Verification of Performance in Result-Based Financing : The Case of Burundi - Renaud, Adrien (World Bank, Washington, DC, 2014)
Paying health facilities incentives based on their performance is one form of results-based financing (RBF). Verification of the performance of the providers is a vital part of RBF program implementation. Burundi was one of the first African countries to introduce performance-based financing (PBF). The PBF scheme is implemented in the whole country and is led by the Ministry of Health (MoH). It pays incentives based on quantity of services provided as well as a quality of care component. This study describes the methods used for verification in Burundi, which include monthly verification of the quantity and technical quality of services provided on a quarterly basis; semiannual patient tracing and assessment of patient satisfaction; and counter-verification of the information provided by these three mechanisms. The results of verification are presented and it discusses obstacles to verification, how they have been addressed, and the challenges ahead. The case study is part of a broader analysis, which includes multiple country case examples, to expand knowledge about the verification process and practices to address the design and implementation needs of RBF programs.